(untitled) (Research, Society and Development, 2021)
Soccer is a dynamic sport that requires different skills and abilities from its participants. Motor skills are very present in the sport of soccer, with a set of movements being performed, which is fundamental in sports practice and in the selection of young talents. Given the limited number of review studies that address the analysis of motor skills in soccer players, especially among younger people, this study aimed to assess motor skills in under-15 soccer students. An integrative review was carried out using the Scielo, Pubmed and Lilacs databases. The analysis considered publications from 2010 to 2021, in Portuguese, English and Spanish. It was found that motor skills express a degree of coordination of movements, developing faster when stimulated since childhood, an individual can have different skills for each function, being the sport skill necessary for all sports. Motor skill proved to be important for soccer, including talent selection and personal development. Further studies in the field are needed and should provide more evidence for elite young athletes, as specifically these early years in a player’s career are crucial for skill development.